Psychological Perspective of Doping in Recreational Sports Among High School Students in Nigeria - Olufemi Adegbola Adegbesan; Oluwatoyin Mercy Jayeoba; AbduRahman Adebayo Owoade (Indonesian Journal of Sport Management, 2025)
Recreational sports are expected to be free from unhealthy competition and mainly for the purpose of fun and enjoyment. However, it has been discovered that doping practices in the form of performance enhancement drugs has gone beyond competitive sports and extended to recreational sports. The goal of this study is to gather psychological perspectives leading to doping among high school students with an insight on behavioral and motivational factors. Participants included 600 high school students from across the country. Participation was voluntary. Mixed methods of quantitative and in-depth interviews were used to collect data. descriptive statistics, correlations, regression analyses were used for inferential tests. Findings indicated that; 51% of the respondents were Male while 49% was female. The statistical significance for testing was at 0.05. the study shows that self-control and moral disengagement have significant relationships with doping in recreational sports. It was concluded that awareness of the psychological basis of doping among participants in recreational sports in high schools in Nigeria is essential in order to curb doping practices and protect the main spirit and purpose of recreational sports which is for fun and enjoyment.